The Price of Fixed Income Market Volatility - Mele, Antonio; Obayashi, Yoshiki (Springer Finance, 2015)
Fixed income volatility and equity volatility evolve heterogeneously over time, co-moving disproportionately during periods of global imbalances and each reacting to events of different nature. While the methodology for options-based "model-free" pricing of equity volatility has been known for some time, little is known about analogous methodologies for pricing various fixed income volatilities. This book fills this gap and provides a unified evaluation framework of fixed income volatility while dealing with disparate markets such as interest-rate swaps, government bonds, time-deposits and credit. It develops model-free, forward looking indexes of fixed-income volatility that match different quoting conventions across various markets, and uncovers subtle yet important pitfalls arising from naïve superimpositions of the standard equity volatility methodology when pricing various fixed income volatilities. The ultimate goal of the authors´ efforts is to make interest rate volatility standardization a valuable channel of information, helping design signal generation and trading strategies, or, to mention another example, informing policy makers about how decisions and communication affect ongoing developments in fixed income volatility. More generally, this work will help inform the public about how uncertainty is perceived by key players in one of the most important segments in the whole capital market.